IDENTIFICATION, SEPARATION, AND CHARACTERIZATION OF DEGRADATION PRODUCTS OF TRIAMCINOLONE HEXACETONIDE USING LC AND LC-MS/MS - SUNIL MAHAJAN, BHAVNA; MINIYAR, PANKAJ B. (International Journal of Applied Pharmaceutics, 2024)
Objective: The study aimed to separate the forced degradation products of Triamcinolone hexacetonide using HPLC and characterize the degradation product by LC-MS/MS fragmentation pattern. Methods: Triamcinolone hexacetonide (THA) and its primary degradation products were identified using a liquid chromatography-mass spectrometry/Mass spectrometry (LC-MS/MS) approach. The degradation study was based on in-depth stress testing with acid, base, peroxide, heat, and light. A Zorbax SB C18 column and a greener mobile phase composed of methanol and 10 mmol ammonium acetate buffer in water at pH 3 were employed to accomplish separation and quantitation at a flow rate of 0.7 ml/min in an isocratic mode with a 239 nm detection wavelength. Results: A major degradation product of the drug was obtained in acidic and alkaline stress conditions. The drug was found to be stable for all other stress conditions. The LC-MS/MS analysis results of the active pharmaceutical ingredient and resulting product after degradation were interpreted to identify the novel degradation product and fragments. The developed method was validated as per International Council for Harmonization (ICH) guidelines. The square root of the correlation coefficients, which indicated linearity for THA in 50 to 150 % of the workload, was 0.99. Method Precision assay was performed on six different preparations, percentage relative standard deviation (% RSD) of assay value is 0.17 % and system precision is 0.30 %. In accuracy, overall % RSD of 50 %, 100 %, and 150 % in triplicate is 0.95. Conclusion: It is concluded that the drug is stable to all other stress conditions except for acidic and alkaline stress conditions and generates a novel degradation product. The developed LC (Liquid chromatography) method separates and identifies the degradation product.